(untitled) (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2025)
In the modern globalized world, the quality of education has become a key factor in social and economic development. One of the most important elements of educational quality assurance is assessment. International standards of assessment provide a common framework for evaluating students’ knowledge, skills, and competencies in a fair, reliable, and transparent manner. This article explores the concept of international assessment standards, examines major international assessment programs, and highlights their role in improving the effectiveness of educational systems.